PRINT CULTURE IN SUNDANESE FOR 100 YEARS IN THE DUTCH EAST INDIES - Moriyama, Mikihiro (Universitas Pendidikan Indonesia, 2018)
Sundanese books have been printed since 1850 up to the present. This article tries to draw a configuration of printing books in Sundanese for about 100 years in the Dutch colonial and Japanese occupation period. Printing and publishing books in Sundanese was initiated by the Dutch colonial government for the sake of management of their colony. This article discuss three aspects in print culture in Sundanese: (1) the role of government printing house and private publishers, (2) the cultural relationship between manuscript and printed books (3) the changes after the emergence of printed books. Print culture in the Sundanese-speaking community was born and has developed. Its facets have changed from time to time. We notice more than 2200 Sundanese books were published up to the second decade of the 21st century when the technological innovation has proceeded in an enormous pace. However, the importance of Sundanese publication has not diminished in terms of nurturing educated citizens in this digital-oriented society and supporting cultural identity.Â